Identification of a Two-Component Regulatory Pathway Essential for Mn(II) Oxidation in Pseudomonas putida GB-1 - Geszvain, Kati (American Society for Microbiology (ASM), 2010)
Bacterial manganese(II) oxidation has a profound impact on the biogeochemical cycling of Mn and the availability of the trace metals adsorbed to the surfaces of solid Mn(III, IV) oxides. The Mn(II) oxidase enzyme was tentatively identified in Pseudomonas putida GB-1 via transposon mutagenesis: the mutant strain GB-1-007, which fails to oxidize Mn(II), harbors a transposon insertion in the gene cumA. cumA encodes a putative multicopper oxidase (MCO), a class of enzymes implicated in Mn(II) oxidation in other bacterial species. However, we show here that an in-frame deletion of cumA did not affect Mn(II) oxidation. Through complementation analysis of the oxidation defect in GB-1-007 with a cosmid library and subsequent sequencing of candidate genes we show the causative mutation to be a frameshift within the mnxS1 gene that encodes a putative sensor histidine kinase. The frameshift mutation results in a truncated protein lacking the kinase domain. Multicopy expression of mnxS1 restored Mn(II) oxidation to GB-1-007 and in-frame deletion of mnxS1 resulted in a loss of oxidation in the wild-type strain. These results clearly demonstrated that the oxidation defect of GB-1-007 is due to disruption of mnxS1, not cumA::Tn5, and that CumA is not the Mn(II) oxidase. mnxS1 is located upstream of a second sensor histidine kinase gene, mnxS2, and a response regulator gene, mnxR. In-frame deletions of each of these genes also led to the loss of Mn(II) oxidation. Therefore, we conclude that the MnxS1/MnxS2/MnxR two-component regulatory pathway is essential for Mn(II) oxidation in P. putida GB-1.